The Rebellion Of Tyler In Allen Coulter's Remember Me Movie (2010): A Psychoanalytic Approach - Wardani, Riska Dian Ayu, Drs. Abdillah Nugroho M.Hum, Nur Hidayat S.Pd (2013)
The study gives focus on Psychoanalytic Approach as reflected in Allen Coulter's Remember Me movie. The study investigates how the rebellion influences the personality development of Tyler in Allen Coulter's Remember Me movie especially viewed from psychoanalytic approach. In this research the writer employs the qualitative method. The object of the research is the movie entitled Remember Me by Allen Coulter.In this method, the writer uses two data sources, namely primary data and secondary data sources. The primary data source is the movie itself. The secondary data sources include references and materials related to the study picking up from the books or internet. The method of data collection is literary research and documentation meanwhile the technique of data collection is descriptive technique. Having analyzed the movie, the writer concludes two points. First, based on the structural analysis, Allan Coulter wants to convey an idea that someone has a rebellious soul because the past experience. Second, based on the psychoanalytic analysis, the result of the study reveals the rebellion of Tyler who gets some influences from his life. Remember Me movie represents Allen Coulter's response to the role of environment in influencing and shaping someone's characters of personality. In this case, rebellion is reflected by id, ego, and superego. Key Word: Remember Me, Rebellion, Tyler, Psychoanalytic Approach